Characteristics and functional properties of gelatin extracted from squid (Loligo vulgaris) skin. (January 2016) - Abdelmalek, Baha Eddine; Gómez-Estaca, Joaquín; Sila, Assaâd; Martinez-Alvarez, Oscar; Gómez-Guillén, M. Carmen; Chaabouni-Ellouz, Semia; Ayadi, Mohamed Ali; Bougatef, Ali
Abstract: The characteristics and functional properties of gelatin extracted from squid skin ( Loligo vulgaris ), using commercial pepsin at a level of 15 Units/g skin, were investigated. The gelatin extraction yield was 6.82 g/100 g wet basis, showing high protein content and low fat and ash contents. SDS-PAGE of squid skin gelatin showed high band intensity for the major protein components, especially, α- and β-components. The amino acid profile of squid skin gelatin showed a high percentage of imino acids, essential amino acids and hydrophobic amino acids. Fourier transformed infrared spectroscopy (FT-IR) spectra showed helical structure. Squid skin gelatin was able to form a completely thermo-reversible gel. Gelatin possessed interesting functional properties, which were governed by gelatin concentration. Highlights: This is the first report of the extraction of gelatin from Loligo vulgaris skin. The amino acid profile of squid skin gelatine showed a high percentage of imino acids. Gelatin has a good quality with desirable interfacial properties.